Preclinical evaluation of a tailor-made DOTA-conjugated PSMA inhibitor with optimized linker moiety for imaging and endoradiotherapy of prostate cancer - Benes̆ová, Martina; Afshar-Oromieh, Ali; Kratochwil, Clemens; Mier, Walter; Haberkorn, Uwe (Journal of nuclear medicine, 2015)
Despite many advances in the past years, the treatment of metastatic prostate cancer still remains challenging. In recent years, prostate-specific membrane antigen (PSMA) inhibitors were intensively studied to develop low-molecular-weight ligands for imaging prostate cancer lesions by PET or SPECT. However, the endoradiotherapeutic use of these compounds requires optimization with regard to the radionuclide-chelating agent and the linker moiety between chelator and pharmacophore, which influence the overall pharmacokinetic properties of the resulting radioligand. In an effort to realize both detection and optimal treatment of prostate cancer, a tailor-made novel naphthyl-containing DOTA-conjugated PSMA inhibitor has been developed. Methods: The peptidomimetic structure was synthesized by solid-phase peptide chemistry and characterized using reversed-phase high-performance liquid chromatography and matrix-assisted laser desorption/ionization mass spectrometry. Subsequent 67/68Ga and 177Lu labeling resulted in radiochemical yields of greater than 97% or greater than 99%, respectively. Competitive binding and internalization experiments were performed using the PSMA-positive LNCaP cell line. The in vivo biodistribution and dynamic small-animal PET imaging studies were investigated in BALB/c nu/nu mice bearing LNCaP xenografts. Results: The chemically modified PSMA inhibitor PSMA-617 demonstrated high radiolytic stability for at least 72 h. A high inhibition potency (equilibrium dissociation constant [Ki] = 2.34 ± 2.94 nM on LNCaP; Ki = 0.37 ± 0.21 nM enzymatically determined) and highly efficient internalization into LNCaP cells were demonstrated. The small-animal PET measurements showed high tumor-to-background contrasts as early as 1 h after injection. Organ distribution revealed specific uptake in LNCaP tumors and in the kidneys 1 h after injection. With regard to therapeutic use, the compound exhibited a rapid clearance from the kidneys from 113.3 ± 24.4 at 1 h to 2.13 ± 1.36 percentage injected dose per gram at 24 h. The favorable pharmacokinetics of the molecule led to tumor-to-background ratios of 1,058 (tumor to blood) and 529 (tumor to muscle), respectively, 24 h after injection. Conclusion: The tailor-made DOTA-conjugated PSMA inhibitor PSMA-617 presented here is sustainably refined and advanced with respect to its tumor-targeting and pharmacokinetic properties by systematic chemical modification of the linker region. Therefore, this radiotracer is suitable for a first-in-human theranostic application and may help to improve the clinical management of prostate cancer in the future.